1983
DOI: 10.1083/jcb.96.3.613
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular calcium depletion on membrane topography and occluding junctions of mammary epithelial cells in culture.

Abstract: Ca 2+ dependence of occluding junction structure and permeability, well documented in explanted or cultured epithelial sheets, presumably reflects inherent control mechanisms. As an approach to identification of these mechanisms, we induced disassembly of zonulae occludentes in confluent monolayers of mouse mammary epithelial cells by exposure to low concentrations of the chelators, EGTA or sodium citrate. Stages in disassembly were monitored during treatment by phase-contrast microscopy and prepared for trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

1986
1986
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 67 publications
(76 reference statements)
3
75
0
Order By: Relevance
“…The mammary epithelium is also a polarised epithelium and in the first experiment we confirmed that in mammary cells Ca sensitivity is indeed mediated only via the apical membrane. Moreover, we also confirmed earlier studies showing that extracellular Ca levels can influence TJ status (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. Thus, for PTHrP to have an effect on mammary TJs it would have to act on the apical side of the cell.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The mammary epithelium is also a polarised epithelium and in the first experiment we confirmed that in mammary cells Ca sensitivity is indeed mediated only via the apical membrane. Moreover, we also confirmed earlier studies showing that extracellular Ca levels can influence TJ status (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. Thus, for PTHrP to have an effect on mammary TJs it would have to act on the apical side of the cell.…”
Section: Discussionsupporting
confidence: 76%
“…Moreover, maintaining extracellular Ca levels, presumably to facilitate adequate intracellular levels of Ca, is a prerequisite for preventing mammary TJ breakdown in vitro and in vivo (Neville & Peaker 1981, Pitelka et al 1983, Stelwagen et al 1995. The role of PTHrP in maintaining cellular Ca homeostasis and Ca transport in epithelia, including that of the mammary gland, is well recognised (Seitz et al 1993, Philbrick et al 1996, Friedman 2000, Lafond et al 2001.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitelka et al observed centripetal movement of the cortex of epithelial cells when centrifugal tethering was disrupted by chelation of extracellular calcium (11). Kolodney and Wysolmerski observed that thrombin increased centripetal isometric tension in cultured human umbilical vein endothelial cells (HUVEC) 1 (6).…”
Section: Introductionmentioning
confidence: 99%
“…To confirm that the absence of apical polarity primes cells to enter the cell cycle regardless of the method used to alter apical polarity, we performed similar experiments with S1 acini treated with EGTA. In different cell models, it has been shown that chelation of Ca 2+ by EGTA induces the loss of tight junction organization and thus, apical polarity (Pitelka et al, 1983;Bhat et al, 1993). Treatment of S1 acini with 1.5 mM EGTA efficiently altered apical polarity as shown by the absence of apical location of ZO-1 in the majority of the acini population after 24 hours of incubation (Fig.…”
Section: Journal Of Cell Science 120 (9)mentioning
confidence: 99%